The Dynamics of Social Economic in Object Tourism in Ulo Sumberejo Jember Regency in 2003-2015 - Delila Putri Samjaya; Kayan Swastika; Mohammad Na'im (JURNAL HISTORICA, 2018)
The dynamics of community life around ulo coastal tourism in Jember district have increased, both in terms of economic income increase and socio-cultural changes that occur. The problems in this research are; how is the history of the establishment of Watu Ulo as a tourist attraction ?; and how is the socio-economic life of the people in Watu Ulo Sumberejo village around 2003 ?; and how is the dynamics of socio-economic life of the people in Watu Ulo Sumberejo village in 2003-2015?. The purpose of this research is to analyze the history of the establishment of Watu Ulo as a tourist attraction, and to analyze the socio-economic life of people in Watu Ulo Sumberejo village around 2003, and to analyze the dynamics of socio-economic life of the people in Watu Ulo Sumberejo village in 2003-2015. The research method used is historical research method. The conclusion of this research is the existence of changes and the development of social life that occurred in the community around ulo beach tourism with the increasing of economic sector and socio-cultural change with cultural exchange brought by the visitors Keywords: Dynamics, Social-Economy, Watu Ulo